A Retrospective Comparative Functional and Aesthetic Outcome Study of Muscle versus Cutaneous Free Flaps for Distal Upper Extremity Reconstruction - Thomas, Benjamin; Warszawski, Jan; Falkner, Florian; Nagel, Sarah S.; Vollbach, Felix; Gazyakan, Emre; Schmidt, Volker J.; Kneser, Ulrich; Bigdeli, Amir K. (Journal of Reconstructive Microsurgery, 2021)
Background Function and cosmesis are crucial in upper extremity reconstruction. Yet, there persists a lack of outcome evaluations, particularly regarding differences between free flap types.Methods In a single-center retrospective analysis, outcomes were compared between patients with cutaneous or muscle free flaps for distal upper extremity reconstruction between 2008 and 2018. The Disabilities of Arm, Shoulder and Hand -Score, Michigan-Hand (MHQ), and Short Form 36 Health Survey (SF-36) Questionnaires were assessed, motor function was quantified, and self-reported measures of cosmesis were compared, including the Vancouver Scar-Scale (VSS), MHQ aesthetics-subscale (MAS), and Moscona's cosmetic validation-score (CVS).Results One-hundred forty-one cases were identified, with a shift toward cutaneous flaps over the study period. Muscle flaps were used for larger defects (251 vs. 142 cm2, p = 0.008). Losses, thromboses, and donor-site complications were equally distributed. Partial necroses were more frequent in muscle flaps (11 vs. 1%, p = 0.015). Seventy patients with 53 cutaneous versus 17 muscle flaps were reexamined. There was no difference in the timing of flap coverage (after 16 vs. 15 days, p = 0.79), number of preceding (2 vs. 1.7, p = 0.95), or subsequent operations (19/53 vs. 5/17, p = 0.77). Patients with cutaneous flaps showed higher grip strength (25 vs. 17 kg, p = 0.046) and reported better hand function (MHQ: 58 vs. 47, p = 0.044) and general health (SF-36: 70 vs. 61, p = 0.040), as well as more favorable appearance (MAS: 71 vs. 57, p = 0.044, CVS: 77 vs. 72, p = 0.048), and scar burden (VSS: 0 vs. 3, p < 0.001).Conclusion Cutaneous flaps yielded better motor function, self-perceived cosmesis, patient satisfaction, and quality of life in our cohort of distal upper extremity reconstructions.
Keywords: upper extremity; reconstruction; free flap; microsurgery; range of motion; aesthetics; function; patient satisfaction; quality of life